The Load Transfer Properties of Post?Groutable Cable Bolts Used in the Australian Coal Industry - Rob Thomas (International Conference on Ground Control in Mining, 2012)
Adequate load transfer is considered essential for optimum ground support and is increasingly important in weak roof and/or high stress environments. If adequate load transfer is achieved not only can this have a positive impact on the resulting roof behavior, but it may also allow the use of lower and hence more economic densities of roof support. A wide variety of post-groutable cable bolts are currently in use in the Australian coal mining industry, each of varying capacity, design, and grouting methodology. Though all of the cables are supplied with the appropriate steel specification, strength, and modulus data, the Australian coal mining industry does not have access to a comprehensive and comparative database on the corresponding load transfer performance, which is a critical problem. On the basis of the above, this paper describes the methodology and results of a laboratory pull testing program that aims to assess the impact of cable bolt design on load transfer, and specifically, the impact on the capacity and stiffness of the anchorage. As part of the testing program, 19 cables were tested including (1) plain-strand cables installed in holes drilled with 28 to 55 mm diameter drill bits and (2) bulbed and nutcaged cables installed in holes drilled with 42 to 64 mm diameter drill bits. Other parameters assessed included the significance of smooth and profiled wire, wire packing, and expanded geometry bulbs. The main results of the testing indicate that in comparison to plain-strand cables, if the cable is bulbed or nutcaged, the capacity of the anchor can increase by up to 400%, and the peak stiffness by between one and two orders of magnitude. The results also indicate that increasing hole diameter may have a positive impact on load transfer in the case of bulbed or nutcaged cables and a negative impact on plain-strand cables. No conclusive results were obtained with regard to the impact of grout strength on load transfer.